Framing Pemberitaan Media Televisi Berita Terhadap Figur 'Habib' - Puji Santoso (Jurnal Ilmu Komunikasi, 2021)
Most Muslims in Indonesia believe that the 'habaib' (the plural of the word 'habib') have a lineage from the Prophet Muhammad SAW, so their existence must be glorified and respected. Television media responded to this in various ways. The careers of the Habib expanded not only in the field of Islamic da'wah but also in politics, as shown by figures such as Habib Rizieq Shihab and the former organization he led, the Islamic Defenders Front (FPI). Television media highlighted the political roles of these habibs with various news constructions. The purpose of this study is to analyze the perspective of television media in framing news about the figure of Habib Rizieq Shihab and claims to be descendants of the Prophet Muhammad SAW and to find a model for framing television media in reporting about 'Habib' in the perspective of claiming descendants of the Prophet Muhammad SAW. This research uses the constructivism paradigm with qualitative research method with framing analysis approach. Namely through data collection techniques through several news broadcasts on three television media, interviews, and observations. The results of this study conclude that every television media report that reports about Islamic figures of Arab descent in Indonesia always brings up models and perspectives of news about the object being reported. The many roles of Habib such as Habib Rizieq Shihab are viewed with different perspectives by the news television media. Some Indonesian citizens of Arab descent who are predicated as 'habib' provide different perspectives for television coverage such as KompasTV, MetroTV, and TVOne. The television media KompasTV and MetroTV do not always agree that their reporting about the activities of the 'habaib' is related to the lineage of descendants of the Prophet Muhammad SAW.